Sustainable Tourism Development Impact at Small Island Tourism Destination at Timor-Leste; A Systematical Literature Review - Widia Nascimento Amaral Vong, Emanuel; Sri Endang P, Anastasia; Vong, Manuel da Canossa; Aulia, Tiara Faza (JMET: Journal of Management Entrepreneurship and Tourism, 2024)
Sustainable tourism development (STD) is important for developing tourist destinations with the specifics of small islands such as Atauro Island, Jaco Island, and Timor Island in Timor-Leste. This research aims to obtain several variables for sustainable tourism development based on positive and negative impacts on economic, social, and environmental goals, and to form an analytical conceptual framework through the As6 variable applied to the sustainable tourism development on small islands in Timor-Leste. This research adopts the systematic literature review (SLR) to investigate impacts of the As6 variable. This research considered the methodological process of developing an analytical framework for STD with an initial search process using the keyword impact of tourism development, 60 papers were identified, followed by the next combination of keywords, the impacts of sustainable tourism development on small islands, resulting in 29 papers, and in the third stage of the search continued by using the keyword impact of sustainable tourism development on the small island of Timor-Leste combined with variable As6, only 7 papers were identified. This research has temporarily resulted in the formation of an analytical framework concept which can be concluded that sustainable tourism development with all its impacts describes complex interactions between humans and environmental, social, and economic systems from an AS6 perspective.